Study of pharyngocutaneous fistula after total laryngectomy - IDE, Shinsuke; TONO, Tetsuya; KAJIHARA, Kei; OKUDA, Takumi; KAWABATA, Takayuki (jibi to rinsho, 2021)
We investigated the incidence and risk factors of pharyngocutaneous fistula (PCF) after total laryngectomy. The study subjects were 36 patients who had received total laryngectomy at Miyazaki University Hospital between April 1, 2013, and December 31, 2019. PCF developed in 9 patients (25%). This rate was even higher among patients with diabetes (3/6 ; 50%). However, we should have evaluated the disease severity of diabetes at the degree of the tissue disorder, and not at the blood sugar level. The incidence of PCF in salvage cases was 31.6% (6/19). As a result, we concluded that the operation using the prophylactic flaps for all salvage cases was somewhat excessive. In the future, we will continue to deal with the PCF by early treatment.